2018
DOI: 10.1111/cfs.12454
|View full text |Cite
|
Sign up to set email alerts
|

Relationship to parents in adulthood with a background of out‐of‐home care in childhood

Abstract: The longitudinal study started with children aged up to 4 who had been taken into care because of unacceptable living conditions and deficient parental care. After their initial stay in a children's home, the 26 children in the research group went on to have diverse placement histories throughout their childhood (up to age 18). The children have been divided into 4 subgroups in accordance with the length of time they lived with 1 of their parents or with foster parents. Relationships were 1 of the themes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Many participants distanced themselves from their birth parents because of frustration over communication or meetings with them. Deliberating over whether to maintain or avoid contact with birth parents has also been recognised in previous studies (Andersson, 2018;Chateauneuf et al, 2018;Moyers et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Many participants distanced themselves from their birth parents because of frustration over communication or meetings with them. Deliberating over whether to maintain or avoid contact with birth parents has also been recognised in previous studies (Andersson, 2018;Chateauneuf et al, 2018;Moyers et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Research supports the beneficial effects of keeping in touch with birth parents (Atwool, 2013;McWey & Mullis, 2004), but some children and youth experience the relationship as taxing and do not wish to see them (Lundström & Sallnäs, 2009;McWey et al, 2010). According to Franzén and Vinnerljung (2006), it is not uncommon for foster care children and youth to lose a birth parent before the age of 18 years, which can result in further emotional load (Andersson, 2018).…”
Section: Challenges and Adversities In The Lives Of Foster Care Children And Youthmentioning
confidence: 99%
“…Further, 81% of respondents reported having weekly contact with a biological family member. In contrast, a recent Swedish study found problematic relationships often develop between care leavers and their birth parents over time, particularly if the problems facing the birth parents remain (Andersson, 2018). The connection among birth family members often survives lengthy disruption and continuing difficulties (Courtney and Hughes-Heuring, 2005; Samuels and Pryce, 2008).…”
Section: Evolving Relationshipsmentioning
confidence: 97%
“…Children who grow up without parental care have already had adverse experiences in childhood, which foster a profound distrust of people and the world that has a long‐term impact on their ability to thrive (Gorina & Sukste, 2019). Andersson (2018) found that adults who had out‐of‐home care in childhood reported mixed feelings about their parents and tended to keep them at a distance, with almost none claiming to have a close relationship with their parents. Children in residential care do not put a high importance on their relationships with their parents, which are characterized by lack of trust, uncertainty, and a perception of the birth family's inadequate capacity to support their needs (Bejenaru & Tucker, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the perspective of parents has not been sufficiently examined.Maintaining the parent-child relationship while a child is in the child welfare system is a common challenge worldwide. Adults who received out-of-home care during childhood report mixed feelings about their parents, with almost none claiming to have a close relationship with their parents (Andersson, 2018). When comparing their relationships with biological parents versus with childcare workers, children perceive their parents as more vulnerable and trust them less, which is understandable given that most of their parents have difficult backgrounds or living conditions (Maaskant et al, 2016).…”
mentioning
confidence: 99%